Current estimates of Philippine marine mollusks taxonomic diversity - Garcia, Abigail S.; Anticamara, Jonathan A. (2023)
Mollusks are among the most diverse and the most threatened invertebrate groups, with
high records of recent extinctions. Yet, the assessment of mollusk diversity and records in
megadiverse countries such as the Philippines greatly needs synthesis and updating. Here, we report on the current taxonomic diversity of the Philippine mollusk. Comprehensive records of mollusks in the Philippines from published literature, accessible museum records, and online databases were compiled and checked with the World Register of Marine Species. A total of 64,898 Philippine mollusk records were compiled, comprised of 14,482 distinct species. Of these distinct species records of Philippine mollusk, 51% have accepted names in WoRMS, whereas 35.8% had taxonomic name changes; 1.5% had unaccepted names in WoRMS but with no accepted names either (e.g. taxon inquirendum, nomen dubium, etc), and 11.7% did not have exactly matched records in WoRMS. After checking all Philippine mollusks records against WoRMS, there were 8,066 mollusk species in the Philippines belonging to 1,991 genera within 423 families and 51 orders, representing all molluscan classes. A total of 7,085 (88%) of the species records were marine (6,953 or 86% were strictly marine species) belonging to 1,780 genera, 368 families, and 50 orders, also representing all mollusk classes. This current account is the most comprehensive we know to date, but it certainly is an underestimate, as not all possible resources are accessible. A systematic national-scale survey of Philippine mollusk diversity is needed to improve the current account and to fill the gaps in [1] taxonomic status verification, and [2] the IUCN and conservation status of many Philippine mollusk species (which, to date, 96% of all species have no IUCN assessments).
Keywords: Mollusks; Marine species diversity; Taxonomy